The IFMIF-DONES fusion oriented neutron source: evolution of the design. (9th December 2021) - Królas, W.; Ibarra, A.; Arbeiter, F.; Arranz, F.; Bernardi, D.; Cappelli, M.; Castellanos, J.; Dézsi, T.; Dzitko, H.; Favuzza, P.; García, A.; Gutiérrez, J.; et al.
Abstract: IFMIF-DONES is a powerful neutron irradiation facility for the study and qualification of materials planned as part of the European roadmap to fusion-generated electricity. Its main goal is to study properties of materials under severe irradiation in a neutron field similar to the one in a fusion reactor first wall. It is a key facility to prepare for the construction of the DEMO power plant envisaged to follow ITER. The decision to start the construction of IFMIF-DONES is expected imminent. In this paper we present and discuss several key technical studies and decisions to improve and optimize the engineering design of IFMIF-DONES which were carried out as part of the activities in the framework of the EUROfusion Early Neutron Source work package (2015–2020). The following topics are discussed in this paper: the new layout of the IFMIF-DONES SRF LINAC accelerator and high-energy beam transport line, 7 Be impurity management approach for the lithium loop, a maintainable test cell concept, a revised layout of the access cell for the remote maintenance operations, and facilities for complementary experiments.